Analisis Kepuasan Wisatawan terhadap Fasilitas dan Layanan di Destinasi Wisata Alam - Soraya Annisa Rani (Lembaga Penelitian dan Pendidikan, 2025)
Tourist satisfaction is a key indicator of the success and sustainability of natural tourism destinations. This study aims to analyze tourist satisfaction with the facilities and services provided at a natural tourism destination. The research employed a quantitative descriptive method with survey techniques distributed to 200 visitors. Data were analyzed using descriptive statistics and customer satisfaction index (CSI). The results show that the overall satisfaction level is in the “satisfied” category, with the highest satisfaction derived from natural beauty and cleanliness, while the lowest comes from the availability of supporting facilities such as parking areas and public restrooms. The findings indicate that while the destination is attractive in terms of its natural resources, service quality and supporting facilities still need improvement. This study contributes to the literature by providing insights into the relationship between visitor satisfaction and sustainable tourism management. The implications suggest that destination managers should prioritize investments in infrastructure and service quality to maintain competitiveness and encourage repeat visits.